Paradoxical impact of government social expenditures on the resilience of small enterprises under economic instability: an empirical analysis - Shandova, N.; Stemkovskyy, V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The article examines the impact of social expenditures on the resilience of small enterprises under conditions of economic instability and structural transformations. Theoretical approaches and empirical evidence from EU and OECD countries demonstrate that the relationship between the level of social spending and the resilience of small firms is neither linear nor unambiguous. The findings indicate that, depending on the scale of social expenditures, the fiscal capacity of the state, and the overall macroeconomic environment, their influence may vary, displaying both stabilizing and constraining effects. Moderate levels of social spending help reduce the risk of small enterprises bankruptcies by supporting domestic consumer demand, mitigating social disparities, and enhancing the predictability of the economic environment. At the same time, excessive expansion of social programs under conditions of limited budgetary resources may lead to increased fiscal pressure, reduced investment capacity, and the emergence of institutional barriers to entrepreneurial development. The study emphasizes that the intensity and direction of the impact of social expenditures are largely shaped by crisis or post-crisis economic conditions. During periods of instability, the positive effects of social spending become more pronounced, whereas in stable phases, the likelihood of accumulating long-term fiscal risks increases. Particular attention is given to the Ukrainian context, where the role of social expenditures has significantly expanded due to wartime conditions and the need to ensure basic social support. It is determined that a key challenge for Ukraine is to find an optimal balance between the necessity of social protection for the population and the need to create a favorable environment for the development of small businesses. Based on the obtained results, the study formulates practical recommendations aimed at optimizing the structure of social expenditures, strengthening their targeting, improving institutional mechanisms for small enterprises support, and introducing approaches sensitive to threshold and contextual effects. The study concludes that the effectiveness of social spending in ensuring the resilience of small enterprises depends not so much on its absolute volume, but on its strategic alignment with the state’s economic capacities, structural priorities, and the quality of the institutional environment.